Airflow efficacy of ballpoint pen tubes: a consideration for use in bystander cricothyrotomy. Issue 4 (12th April 2010) - Owens, David; Greenwood, Ben; Galley, Alistair; Tomkinson, Alun; Woolley, Sarah
Abstract : Objective: To examine the suitability of commonly available ballpoint pens as a substitute emergency tracheostomy tube. Methods: commonly available ballpoint pens were examined and compared against two standard cricothyroidotomy sets. The pens were evaluated for dimensions, speed of construction of a temporary tracheostomy tube and airway resistance with differing flow rates. Results: Internal diameters of the pens varied considerably. Time taken to construct a temporary tube ranged from 3 to 170 s, and in the majority of pens the airway resistance increased dramatically as the airflow rate increased. Conclusion: Contrary to popular belief, the majority of ballpoint pens appear unsuitable for use as a substitute tracheostomy tube. In this study only two pens fulfilled the criteria for use: the Baron retractable ballpoint and the BIC soft feel Jumbo.